2015
DOI: 10.1016/j.vaccine.2015.04.008
|View full text |Cite
|
Sign up to set email alerts
|

HIV-associated memory B cell perturbations

Abstract: Memory B-cell depletion, hyperimmunoglobulinemia, and impaired vaccine responses are the hallmark of B cell perturbations inhuman immunodeficiency virus (HIV) disease. Although B cells are not the targets for HIV infection, there is evidence for B cell, especially memory B cell dysfunction in HIV disease mediated by other cells or HIV itself. This review will focus on HIV-associated phenotypic and functional alterations in memory B cells. Additionally, we will discuss the mechanism underlying these perturbatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
24
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(31 citation statements)
references
References 99 publications
(189 reference statements)
5
24
0
Order By: Relevance
“…In addition, many changes in the B cell compartment have been reported during HIV infection (reviewed in Refs. 85,86), namely, a reduction in resting memory and an increase in activated and tissue-like exhausted memory B cells subsets. A recent study has also demonstrated that vaccination against influenza A induces IgG-secreting cells in parallel with increases in CD21 2 CD27 + activated memory cells, as well as a reduction in tissue-like CD21 2 CD27 2 memory cells that were exhausted (87).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, many changes in the B cell compartment have been reported during HIV infection (reviewed in Refs. 85,86), namely, a reduction in resting memory and an increase in activated and tissue-like exhausted memory B cells subsets. A recent study has also demonstrated that vaccination against influenza A induces IgG-secreting cells in parallel with increases in CD21 2 CD27 + activated memory cells, as well as a reduction in tissue-like CD21 2 CD27 2 memory cells that were exhausted (87).…”
Section: Discussionmentioning
confidence: 99%
“…HIV dysregulates many aspects of TB immunity by causing chronic immune activation (18), skewing the T reg /T H 17 balance (19), and perturbing B-cell signaling and memory formation (20). HIV further blocks TNF-α-mediated macrophage activation and apoptosis, thus favoring the persistence of Mtb (21).…”
Section: Nonhuman Primate | B Cells | Tuberculosis | Cd4 T Cells | CDmentioning
confidence: 99%
“…However, this hypothesis is dissatisfying for several reasons. First, PEL, like MCD, is highly linked to HIV disease, which, even when well controlled by antiretroviral therapy (ART), is associated with defects in the GC reaction and the depletion of memory B cells [18]; events which would reduce the number and viability of memory B cells as infection targets in the early stages of PEL pathogenesis. Moreover, this hypothesis requires the supposition that KSHV has distinct biological effects leading to different disease states based on the target B cell subtype.…”
Section: Extrafollicular Maturation: Unifying the Viral Pathogenic Modelmentioning
confidence: 99%